An introduction to ethical, safety and intellectual property rights issues in biotechnology - Nambisan, Padma (Elsevier : Academic Press, 2017)
An Introduction to Ethical, Safety and Intellectual Property Rights Issues in Biotechnology provides a comprehensive look at the biggest technologies that have revolutionized biology since the early 20th century, also discussing their impact on society.The book focuses on issues related to bioethics, biosafety and intellectual property rights, and is written in an easy-to-understand manner for graduate students and early career researchers interested in the opportunities and challenges associated with advances in biotechnology.Important topics covered include the Human Genome Project, human cloning, rDNA technology, the 3Rs and animal welfare, bioterrorism, human rights and genetic discrimination, good laboratory practices, good manufacturing practices, the protection of biological material and much more.Full of relevant case studies, practical examples, weblinks and resources for further reading, this book offers an essential and holistic look at the ways in which biotechnology has affected our global society.Provides a comprehensive look at the ethical, legal and social implications of biotechnologyDiscusses the global efforts made to resolve issuesIncorporates numerous case studies to more clearly convey concepts and chart the development of guidelines and legislation regulating issues in biotechnology. Takes a straightforward approach to highlight and discuss both the benefits and risks associated with the latest biotechnologies. - Resumé vydavatel